Emergence and transboundary spread of lumpy skin disease in South Asia - PANKAJ KUMAR; RASHMI REKHA KUMARI; SARITA DEVI; MANOJ KUMAR TRIPATHI; JASPREET SINGH; RAVI KUMAR; MANISH KUMAR (Indian Journal of Animal Sciences, 2021)
Lumpy skin disease (LSD) is an OIE notifiable, transboundary pox viral disease of livestock. LSD is an emerging disease severely affecting livestock economics. The zoonotic potential of the LSD virus has not been extensively studied and reported. In approximately 90 years, the virus dispersed to numerous world locations after its first emergence in Zambia. LSD virus emergence in South Asia prevailed among livestock (cattle and water buffalo) owners due to economic/financial losses. The estimate of the economic impact of LSD in the southern, eastern and southeastern countries suggested direct losses of livestock and production of approximately USD 1.45 billion. In 2019, nearly the same time, the disease was reported for the first time from many bordering countries, such as India, Nepal, China, and Bangladesh. In 2020, the LSD was also recorded in Bhutan, Sri Lanka, Bangladesh, Vietnam and Southeast China. In 2021, it further spread to new countries such as Thailand, Malaysia and Cambodia. Cattle affected with LSD show a characteristic nodular lesion or skin lump over the whole body and may occasionally be associated with systemic signs. Hematophagous arthropod-borne mechanical transmission is considered primary and the most common route; however, other transmission routes related to illegal animal trade have played a role in the emergence of LSD in countries otherwise/earlier free from it. Among serological diagnostic tests, OIE recommends virus neutralization as the standard gold test. Diagnosis in LSD-free countries requires virus isolation and further sequencing of the isolate. Control of LSD is possible by most of the measures applied for rapidly transmitting viral infection, including vaccination. LSD virus-specific vaccines are considered suitable to confer protection to cattle and buffalo over heterologous vaccines. In countries such as India, the lack of a specific policy for LSD at the time of the first onset of this disease, the high density of susceptible unvaccinated populations, unawareness among farmers, veterinarians and prevailing laws of no slaughter of cattle created a favourable situation of its spread to many states. Amid COVID-19, the whole world is in turmoil; the emergence of diseases such as LSD is further lowering the economy, and hence must be reviewed to save and sustain the backbone of the developing country's economy in Southeast Asia.